Zakłady Lasów Państwowych w warunkach gospodarki rynkowej - Kocel, Janusz (Leśne Prace Badawcze, 2011)
The paper presents the results of an efficiency analysis for 18 of the 19 departments of the State Forests, which are responsible for transportation, service and commercial activities, and are subordinated to regional directorates of the State Forests. The research was conducted in 2009. The assessment of work conducted by departments as well as analysis of possible improvements in their activity, which could increase their economic efficiency, was structured in line with a typical business plan. Based on the results of the analysis, the departments were divided into 5 groups. The defined groups included those departments of strategic importance to the State Forests, as well as those which should undertake some additional activities to improve their economic efficiency. The results of the study were used by the State Forest management to define new strategies for individual departments of the State Forests.